2016
DOI: 10.1093/scan/nsw065
|View full text |Cite
|
Sign up to set email alerts
|

The matter of motivation: Striatal resting-state connectivity is dissociable between grit and growth mindset

Abstract: The current study utilized resting-state functional magnetic resonance imaging (fMRI) to examine how two important non-cognitive skills, grit and growth mindset, are associated with cortico-striatal networks important for learning. Whole-brain seed-to-voxel connectivity was examined for dorsal and ventral striatal seeds. While both grit and growth mindset were associated with functional connectivity between ventral striatal and bilateral prefrontal networks thought to be important for cognitive-behavioral cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
61
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 33 publications
3
61
1
1
Order By: Relevance
“…Thus, our results provide additional evidence that growth mindset serves as a potential factor for cultivating grit among adolescent students. In addition, the association between growth mindset and the left DLPFC volume is consistent with previous findings demonstrating an association between growth mindset and RSFC of DLPFC and striatum (Myers et al, ). Using event‐related potentials (ERPs), Mangels, Butterfield, Lamb, Good, and Dweck () revealed that during a test of general knowledge, participants with growth mindsets exhibited lower P3 activity in the anterior prefrontal cortex, which is associated with error correction and conflict detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our results provide additional evidence that growth mindset serves as a potential factor for cultivating grit among adolescent students. In addition, the association between growth mindset and the left DLPFC volume is consistent with previous findings demonstrating an association between growth mindset and RSFC of DLPFC and striatum (Myers et al, ). Using event‐related potentials (ERPs), Mangels, Butterfield, Lamb, Good, and Dweck () revealed that during a test of general knowledge, participants with growth mindsets exhibited lower P3 activity in the anterior prefrontal cortex, which is associated with error correction and conflict detection.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, growth mindset might be a promising construct that can be shaped to improve the grit levels of individuals. In addition, at the neural level, some evidence has indicated that growth mindset and grit share common cortico‐striatal RSFC between the ventral striatum and the DLPFC (Myers et al, ). In light of these findings, growth mindset might mediate the associations between brain structures and grit.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that a larger sample size with even more variability in diligence is needed to detect a stronger correlation between diligence and brain structure and function. This possibility should be investigated in future studies-so far only a handful of studies have investigated neural correlates of diligence and related constructs and very few have probed striatal functioning (Myers, Wang, Black, Bugescu, & Hoeft, 2016;Nemmi, Nymberg, Helander, & Klingberg, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Grit's predictive role has been corroborated in educational, psychological and social constructs, such as mental health (Kleiman, Adams, Kashdan, & Riskind, ), student learning motivation (Myers, Wang, Black, Bugescu, & Hoeft, ), and success in school and the workplace (Eskreis‐Winkler, Shulman, Beal, & Duckworth, ). Within academic settings, empirical studies have repeatedly shown that grit plays a significant role in individual academic success (Akos & Kretchmar, ; Cosgrove, Chen, & Castelli, ; Duckworth & Quinn, ; Hodge, Wright, & Bennett, ), some failed to detect an association between grit and academic achievement (Al‐Mutawah & Fateel, ; Cross, ; Rojas, ).…”
Section: Introductionmentioning
confidence: 96%
“…Grit's predictive role has been corroborated in educational, psychological and social constructs, such as mental health (Kleiman, Adams, Kashdan, & Riskind, 2013), student learning motivation (Myers, Wang, Black, Bugescu, & Hoeft, 2016), and success in school and the workplace (Eskreis-Winkler, Shulman, Beal, & Duckworth, 2014).…”
mentioning
confidence: 95%